Analgesic effectiveness test of kitolod leaf ethanol extract (isotoma longiflora l.) against male white mice (mus musculus) - Inda Dwi Yanti; Angga Bayu Budiyanto; Lukman Hardia (Institute of Computer Science (IOCS), 2026)
This study aims to evaluate the analgesic effectiveness of ethanol extract of Kitolod leaves (Isotoma longiflora L.) in male white mice (Mus musculus). Kitolod leaves are traditionally used as herbal remedies for pain, yet scientific evidence regarding their analgesic potential remains limited. This true experimental research employed a pre- and post-test with control group design, involving five groups: negative control (Na-CMC 1%), positive control (diclofenac sodium 50 mg), and three treatment groups administered Kitolod leaf extract at doses of 56 mg/kgBW, 112 mg/kgBW, and 224 mg/kgBW. Extract preparation was carried out using maceration with 96% ethanol, followed by phytochemical screening which confirmed the presence of flavonoids, alkaloids, tannins, and steroids. Analgesic activity was assessed using the tail flick method by measuring latency response to thermal stimuli at intervals of 30, 60, 90, 120, 150, and 180 minutes post-treatment. The results showed that Kitolod leaf extract increased pain response latency, with the 112 mg/kgBW and 224 mg/kgBW doses demonstrating the strongest analgesic effects comparable to diclofenac sodium. Statistical analysis using independent sample t-test and one-way ANOVA indicated significant differences (p < 0.05) between treatment and control groups. These findings suggest that Kitolod leaf ethanol extract possesses promising analgesic properties and may serve as a potential natural alternative for pain management.